Pengaruh Disiplin dan Lingkungan Kerja Terhadap Prestasi Kerja Karyawan PT. Oto Multi Artha Cabang Pekanbaru - Wahyuni, Wan Zuria; ', Machasin; ', Nuryanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The research was conducted at PT. Oto Multiartha pekanbaru branch roadTambusai Pekabaru lord, this study aimed to determine the effect of discipline and work environment variables simultaneously or partially on work performance of employees of PT. Auto Multi Artha Pekanbaru Branch. The sampling method using census method with a sample size of 62 people. Data collection methods used were interviews directly to parties - parties involved with the issues that are being discussed and gave questionnaires to employees in accordance with the research conducted. Data were analyzed using Qualitative and Quantitative Methods Methods that use that formula Descriptive Statistics, Test Data Quality, Multiple Linear Regression Analysis and Hypothesis Testing, with the help of software SPSS (Statistical Product and Service Solutions). The results showed that simultaneous Discipline of Work and Work workplace significant effect on Employee Job Performance in PT. Oto Multiartha Pekanbaru Branch, partially Variable work Discipline and Working Environment significant effect on employee performance PT. Oto Multiartha Pekanbaru Branch. regression coefficient is positive ( + ) indicates a unidirectional relationship, in other words Discipline and work environment will improve employee work performance at PT. Auto Multi Artha Pekanbaru Branch. Correlation or relationship between the discipline and the work environment Work with employees at PT. Auto Multi Artha Pekanbaru Branch is strong at ( r = 0.743 ) and the coefficient of determination or R square figures amounted to 0.553Keywords: job Discipline, Work Environment and Job Performance